Designing the Policy Model of In-Service Training Suitable for the Professional Development of Teachers - Sotoudeh Moghadam, Maryam; Cherabin, Moslem; Akbari, Ahmad; Zendedel, Ahmad (Iranian Journal of Educational Sociology, 2022)
Purpose: Teachers are one of the most important pillars of the education system and play a crucial role within it. Therefore, the present study aimed to design a model for policy-making on empowerment and professional advancement of teachers, focusing on in-service training. Methodology: This study was applied in terms of objective and mixed in terms of implementation method, i.e., qualitative and quantitative. In the qualitative section, the research population consisted of experts familiar with the research field, 10 of whom were selected using purposive sampling based on theoretical saturation and subjected to semi-structured interviews. Furthermore, in the quantitative section, the research population was teachers in the city of Neyshabur, 384 of whom were selected using random sampling according to the Krejcie and Morgan table and responded to a researcher-made questionnaire. In this study, qualitative data were analyzed using thematic analysis based on grounded theory in MAXQDA software, and quantitative data were analyzed using exploratory factor analysis and structural equation modeling in SPSS and Smart PLS software. Findings: Qualitative findings indicated that causal conditions included three themes: social needs, changes in educational needs, and the creation of individual needs in teachers; the central phenomenon included three themes: value creation, problem solving, and scientific and practical training; contextual conditions included five themes: proper course implementation, course content richness, a suitable environment, proper planning, and teachers' mindset; intervening conditions included six themes: uncommitted and inexpert managers, improper performance evaluation, improper needs assessment, lack of teaching quality in courses, unconventional teaching methods, and a weak motivational system; strategies included ten themes: successful modeling, course content improvement, region-focused planning, accurate and scientific needs assessment of courses, removing teachers' individual barriers, changes in educational systems, improvement of physical conditions, employing experienced and expert instructors, providing motivational frameworks, and a suitable evaluation system; and outcomes included four themes: social outcomes, improvement in teachers' educational performance, job well-being of teachers, and psychological outcomes of teachers. Quantitative findings showed that the factor loading of all themes (except for 6 themes) was above 0.60, and the Cronbach's alpha and composite reliability of all of them were above 0.70. Additionally, the model for policy-making on empowerment and professional advancement of teachers, with emphasis on in-service training, had a suitable fit, and the effect of causal conditions on the central phenomenon, the effect of the central phenomenon, contextual conditions, and intervening conditions on strategies, and the effect of strategies on outcomes were significant (P